Is The Rights Offering Announcement Good or Bad? - Muhammad Asy'ari Ramadhan; Umi Mardiyati; Sholatia Dalimunthe (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2022)
This study aims to determine changes in market reactions on the rights offering based on the purpose of investment and debt repayments. This research indicator uses abnormal return and trading volume activity. The research observation period was carried out 5 days before and 5 days after the effective date with the object of research being all companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The samples collected were 42 companies using the purposive sampling technique. Testing the data using the Wilcoxon Signed Rank Test and paired sample T-test. The test results show that the rights issue for investment purposes has differences in abnormal returns and trading volume activity around the effective date. Meanwhile, there were no differences in abnormal returns and trading volume activity around the effective date for restructuring purposes. From these results, investors are recommended to look at the purpose of using company funds to improve the quality of investment decision-making.